The The Important Role of Self-Regulation in Worldwide EFL Learning Contexts - Wijaya, Kristian (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
Abstract To better cultivate life-long learning characters within EFL learners, they should be well-trained in activating their utmost self-regulation potentials. By becoming more self-regulated academicians, EFL learners will be more capable of controlling their targeted learning environments, resources, strategies, and time in a better purpose to reach the desired learning outcomes. Concerning this belief, this present qualitative library study was run to exhaustively unearth the crucial role of self-regulation in worldwide EFL learning contexts. To fulfill this main research concern, 30 prior self-regulation studies were conscientiously selected to generate a new enlightenment for globalized ELT educators to nurture their learners’ self-regulation growth in varied language learning situations. The obtained major findings unveiled that a higher degree of self-regulation enabled EFL learners to transform into more life-long knowledge seekers fully reaping more fruitful language learning outcomes. For the betterment of this pivotal psychological investigation, a considerable number of self-regulation literature in line with the interconnected nature of other psychological constructs are highly suggestive for future researchers aiming to conduct identical studies. Keywords: self-regulation, library study, worldwide EFL learning contexts